2022
DOI: 10.2478/rrlm-2021-0036
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Resveratrol on Sphingosine-1 and Oxidative/ Nitrosative Stress in an Experimental Heart Ischemia Reperfusion Model

Abstract: Objectives: Resveratrol (RSV) is a natural polyphenolic compound showing significant antioxidant effects. In this study, we aimed to investigate the effects of resveratrol on the sphingosine-1-phosphate (S1P) and oxidative stress biomarkers in hearth ischemia-reperfusion (I/R). Materials and Methods: The biochemical and histopathological effects of RSV on cardiac ischemia-reperfusion injury were investigated through ELISA- and light microscope. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…In addition, the most decrease in 8-iso-PGF2α value was observed in the combined treatment (RSV+B17) group (p<0.05). The antioxidant role of RSV is to compete with coenzyme Q, capture O2-(Superoxide radical) and inhibit lipid peroxidation (Avnioglu et al, 2022). In our study, the low levels of 8-iso-PGF2α in the treatment group may suggest that RSV inhibits lipid peroxidation as a strong antioxidant in vivo.…”
Section: Histopathological Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…In addition, the most decrease in 8-iso-PGF2α value was observed in the combined treatment (RSV+B17) group (p<0.05). The antioxidant role of RSV is to compete with coenzyme Q, capture O2-(Superoxide radical) and inhibit lipid peroxidation (Avnioglu et al, 2022). In our study, the low levels of 8-iso-PGF2α in the treatment group may suggest that RSV inhibits lipid peroxidation as a strong antioxidant in vivo.…”
Section: Histopathological Resultsmentioning
confidence: 56%
“…Antioxidant substances containing phenolic compounds have positive effects on preventing ischemia-reperfusion or minimizing I/R damage (Avnioglu et al, 2022). Grape seed (RSV) contains high amounts of proanthocyanidins in terms of both quantity and quality.…”
Section: Introductionmentioning
confidence: 99%
“…With the re-initiation of blood flow in the ischemic tissue, ROS released into the environment by PMNL, which migrates and settles in the tissue, has an increased destructive effect on the tissue. Various studies have revealed that ROS performs an essential role in I/R injury by initiating lipid peroxidation (Avnioglu et al, 2021). At the same time, ROS increases tissue damage in the body by reacting with biomolecules.…”
Section: Histopathological Resultsmentioning
confidence: 99%
“…By looking at the receptor and ligand structure, it is seen whether the compound carries a functional drug group [16]. Compounds containing the azomethine group (-HC=N-), which were first introduced by Hugo Schiff in 1864 and formed as a result of the reaction of a primary amine with an active carbonyl compound, and which are generally carried out by acid, base catalysis or heat, are called schiff bases [17,18]. Schiff bases are useful chelates because of their ease of preparation, structural variety, and steric and electronic control mechanisms [1].…”
Section: Introductionmentioning
confidence: 99%
“…Reactive oxygen species (ROS) are free radicals produced during oxidative metabolism. ROS can attack nucleic acid, lipids, proteins, polyunsaturated fatty acids and carbohydrates and induce their oxidation, which can lead to oxidative damage such as protein alteration, membrane dysfunction, enzymatic inactivation, and rupture of DNA strains [17]. Therefore, ROS must be cleared by cellular voters.…”
Section: Introductionmentioning
confidence: 99%